Simplified Design of Magnetic Gear by Considering the Maximum Transmission Torque Line - Norhisam Misron; Luqman Mohd Saini; Ishak Aris; Chockalingam Aravind Vaithilingam; Hanamoto Tsuyoshi (Applied Sciences, 2020)
Magnetic gears (MGs) technology is studied widely among research institutions, with several improvements being documented. This development attracts a high amount of attention due to the demand in the development of magnetic gears towards higher performance than the conventional mechanical counterpart. In general, the design is complicated and there is a lack in detailed references for designing an MG for specific transmission torque as required by its application. Trial-and-error approaches have been the norm in achieving the desired torque by referring the existing MGs for the desired value of torque. This paper presents a new simplified approach towards designing an MG for the required torque and size by referring through a Maximum Transmission Torque Line (MTTL) reference. Finite element method (FEM) is used in analyzing randomly designed magnetic gears with various parameters towards the desired values of the MTTL. The proposed approach of MTTL is a new approach to estimate the total volume of permanent magnets (PMs) required for the MG to achieve the desired transmission torque. The reference line is used to generate equation relating the specific parameters of MG to develop the simplified design of MG based on the estimated total volume of PMs. This simplified way details to 8.5% of error in targeting the desired transmission torque, a means and way for the first stage of the MG design approach to reduce the conventional approaches.